2016
DOI: 10.1093/eurpub/ckw206
|View full text |Cite
|
Sign up to set email alerts
|

European studies on prevalence and risk of autism spectrum disorders according to immigrant status—a review

Abstract: After analysing the results of studies conducted in Europe, it is unclear if higher prevalence estimates of ASDs among immigrants in this region reflect true differences, especially considering many potential confounding factors, e.g. genetic, biological, environmental and cultural. Considering the number of people migrating within Europe there is a substantial need to study further the prevalence of ASDs in immigrant groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 48 publications
1
29
0
4
Order By: Relevance
“…Our results indicating that the combination of low levels of language acquisition and high M‐CHAT scores is more likely to occur in children of immigrant than nonimmigrant mothers, and that this excess risk varies according to the mother's region of origin, is concordant with prior studies based on clinical diagnoses [Abdullahi et al, ; Crafa & Warfa, ; Dealberto, ; Kawa et al, ; Ng & de Montigny, ]. Of note, after adjustment for covariates we found that children of first generation North African or francophone Sub‐Saharan African mothers had higher MB‐CDI mean scores than their nonimmigrant French counterparts.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results indicating that the combination of low levels of language acquisition and high M‐CHAT scores is more likely to occur in children of immigrant than nonimmigrant mothers, and that this excess risk varies according to the mother's region of origin, is concordant with prior studies based on clinical diagnoses [Abdullahi et al, ; Crafa & Warfa, ; Dealberto, ; Kawa et al, ; Ng & de Montigny, ]. Of note, after adjustment for covariates we found that children of first generation North African or francophone Sub‐Saharan African mothers had higher MB‐CDI mean scores than their nonimmigrant French counterparts.…”
Section: Discussionsupporting
confidence: 92%
“…Studying immigrants' children in nonclinical samples is particularly important as there is evidence of ethnic diagnostic/referral bias in medical practice [Begeer, Bouk, Boussaid, Terwogt, & Koot, ]. The associated risk of late diagnosis and underdiagnosis [Kawa et al, ] might lead to a higher likelihood of missing problems in immigrants' children when using routine clinical data, and hence result in underestimates of neurodevelopmental inequalities in the population. Furthermore, most children diagnosed with neurodevelopmental conditions, such as ASD, first receive a diagnosis when aged 3 years or older, although signs may be present earlier [Chlebowski et al, ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To illustrate, a study amongst a Somali population living in the UK (Fox, Aabe, Turner, Redwood, & Rai, 2016) reported findings that echo reports from populations resident in the horn or East of Africa (Gona et al, 2016;Tekola et al, 2016;Tilahun et al, 2016) regarding the perceptions of autism, experiences of stigma and unmet needs. Ethnic minority groups in high-income countries tend to be under-diagnosed for ASD and under-represented in autism research populations (Decoteau, 2017;Kawa et al, 2016;Sandy Magaña & Vanegas, 2017).…”
Section: <Table 1 Here>mentioning
confidence: 99%
“…To illustrate, a study amongst a Somali population living in the UK (Fox, Aabe, Turner, Redwood, & Rai, 2016) reported findings that echo reports from populations resident in the horn or East of Africa (Gona et al, 2016;Tekola et al, 2016;Tilahun et al, 2016) regarding the perceptions of autism, experiences of stigma and unmet needs. Ethnic minority groups in high-income countries tend to be under-diagnosed for ASD and under-represented in autism research populations (Decoteau, 2017;Kawa et al, 2016;Sandy Magaña & Vanegas, 2017). Improving our understanding of the cultural dimensions of autism may thus inform initiatives to improve the identification, diagnosis and access to services of ethnic minority populations within high-income countries(La Roche, Bush, & D'Angelo, 2018).…”
Section: <Table 1 Here>mentioning
confidence: 99%